Wykorzystanie słownictwa meteorologicznego w Krzyżakach Józefa Ignacego Kraszewskiego i Henryka Sienkiewicza - Kupiszewski, Władysław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The article deals with the use of meteorological vocabulary by Kraszewski and Sienkiewicz in the novels on the same topic and presents the stylistic functions of this vocabulary. Sienkiewicz achieved greater lexical and artistic variety